Effect of Different Heat Treatments on the Quality and Flavor Compounds of Black Tibetan Sheep Meat by HS-GC-IMS Coupled with Multivariate Analysis - Jiqian Liu; Lijuan Han; Wenzheng Han; Linsheng Gui; Zhenzhen Yuan; Shengzhen Hou; Zhiyou Wang; Baochun Yang; Sayed Haidar Abbas Raza; Abdulaziz Faisal Saleh Alowais; Alaa Ahmed Alraddadi; Anwar Mohammed Alanazi (Molecules, 2022)
There are limited reports about the effect of different heat treatments on the quality and flavor of Black Tibetan sheep meat. The current study examined the effect of pan-frying, deep-frying, baking, and boiling treatment on the quality of Black Tibetan sheep meat; the amino acid, fatty acid, and volatile flavor compounds (VFCs) were investigated by a texture analyzer, ultra-high-performance liquid chromatography (UHPLC), gas chromatography (GC), and headspace-gas chromatography-ion mobility (HS-GC-IMS). The key VFCs were identified through orthogonal partial least squares discrimination analysis (OPLS-DA), and variable importance projection (VIP) values. In addition, Pearson’s correlations between meat quality parameters and key VFCs were examined. The sensory scores, including texture, color, and appearance, of baked and pan-fried meat were higher than those of deep-fried and boiled meat. The protein (40.47%) and amino acid (62.93 µmol/g) contents were the highest in pan-fried meat (p < 0.05). Additionally, it contained the highest amounts of monounsaturated and polyunsaturated fatty acids, such as oleic, linoleic, and α-linolenic acids (p < 0.05). Meanwhile, pan-fried and deep-fried meat had higher amounts of VFCs than baked meat. The OPLS-DA similarity and fingerprinting analyses revealed significant differences between the three heat treatment methods. Aldehydes were the key aroma compounds in pan-fried meat. Importantly, 3-methylbutyraldehyde and 2-heptanone contents were positively correlated with eicosenoic, oleic, isooleic, linoleic, α-Linolenic, and eicosadiene acids (p < 0.05). To sum up, pan-fried Black Tibetan sheep meat had the best edible, nutritional, and flavor quality.